CAMEL DAN TINGKAT KESEHATAN PERBANKAN - Haryanto, Melinda; Hanna, Hanna (Jurnal Akuntansi, 2014)
Abstract: This study aimed to show whether the ratio of CAMEL (Capital, Asset Quality, Management, Earnings and Liquidity) can be used as an indicator in predictingÂ the health of banks in the future. This study was carried out on the banks listed on theÂ Indonesia Stock Exchange in the period 2008-2012. Descriptive analysis and logisticÂ regression analysis are used to analyze the data. Hypothesis testing is done with theÂ normality test, Independent Sample T-Test and Mann Whitney test are used toÂ determine if two sets of data are significantly different from each other. The result ofÂ this research showed that LDR and NIM variables of bank financial conditionhave noÂ significant differents while CAR, ATTM, APB, NPL, P_PPAP, BOPO, ROA, and ROE have a significant differents. Hyphothesis testing result found that CAR, ATTM, APB, NPL, NIM, and LDR variables did not affected bank financial condition significantlyÂ while P_PPAP, ROA, ROE, and BOPO variables affected bank financial condition significantly. Â